What ASEAN Must Learn from Timor-Leste: A Tripartite Analysis on Australian Foreign Policy Related to Timor Sea Treaty 2018 - Kusumawardhana, Indra; Saptarani Dewi, Gustin (Centre for Business and Diplomatic Studies (CBDS) Bina Nusantara University, 2023)
The Timor Gap had been a hotspot of territorial dispute between Australia and Timor-Leste. In 2018, Australia finally agreed to settle a permanent maritime boundary in favour of Timor-Leste. Why was Australia willing to sacrifice the border and give a favourable outcome to Timor-Leste? The research examined the importance of the tripartite approach to Foreign Policy analysis to understand why a country may choose seemingly unfavourable options in territorial disputes. The analysis showed how Australian foreign policy was influenced by agency-structure interactions within the international system. The research demonstrated that structural constraints at the international level influenced Australia’s decision, including the South China Sea dispute between ASEAN members and China, previous agreements Australia-Timor-Leste on the management of the Timor Gap, and domestic political dynamics in Australia. The research reveals a relationship between actors’ structural and dispositional dimensions in foreign policy. In the case of Australia, there is a strong link between democratic values ​​and respect for the international rules-based order. Altogether, this situation prompted Australia to continue negotiations with Timor-Leste over the Timor Gap and ultimately to accept an agreement for maritime delimitation in Timor-Leste’s favor.